WS2/CsPbBr3 van der Waals heterostructure planar photodetectors with ultrahigh on/off ratio and piezo-phototronic effect-induced strain-gated characteristics. (November 2019) - Xu, Qian; Yang, Zheng; Peng, Dengfeng; Xi, Jianguo; Lin, Pei; Cheng, Yang; Liu, Kaihui; Pan, Caofeng
Abstract: High-performance, low-power and multifunction-integrated devices are crucial in emerging technologies. Herein, we demonstrate WS2 /CsPbBr3 van der Waals heterostructure (vdWH) planar photodetectors combining the high mobility of mechanically exfoliated 2D WS2 nanoflakes with the remarkable optoelectronic properties of 1D single-crystalline CsPbBr3 nanowires and the strain-gated and strain-sensing characteristics induced by the piezo-phototronic effect. Owing to the effective charge carrier transfer and channel depletion originating from the appropriate energy band alignment, collaborative improvement of the photocurrent and dark current is realized, thus, an ultrahigh on/off ratio of 10 9.83 is achieved. The highest responsivity and detectivity at V d  = 2 V are 57.2 A W −1 and 1.36 × 10 14 Jones, respectively. Even with a lower V d of 0.5 V, decent performance is still obtained. Furthermore, the interfacial carrier transfer can be manipulated through the piezo-phototronic effect induced by CsPbBr3 monocrystal nanowires. Thus, when constructed on a flexible PEN substrate, the WS2 /CsPbBr3 vdWH planar photodetector presents strain-gated photocurrent and responsivity, modulated by a factor of 11.3 with strain application, and a strain-sensing function is simultaneously realized due to the linear dependence of the photocurrent on strain. This unprecedented device design opens up a new avenue toward not only high-performance and low-power but also multifunction-integrated devices realized by the direct effect of mechanical inputs on charge carriers. Graphical abstract: 2D-WS2 /1D-CsPbBr3 vdWH planar photodetectors are assembled and characterized. Light-induced carrier transfer to WS2 and depletion of the WS2 channel enable simultaneous increase of the photocurrent and decrease of the dark current. Furthermore, the piezoelectric property of monocrystalline CsPbBr3 nanowires endow WS2 /CsPbBr3 photodetectors with strain-gated characteristics and a strain-sensing function induced by the piezo-phototronic effect.Image 1 Highlights: WS2 /CsPbBr3  van der Waals heterostructures (vdWHs) are built, and WS2 /CsPbBr3  vdWH planar photodetectors are constructed.. Ultrahigh on/off ratio up to 10 9.83 is obtained within  V d of 2V. The highest detectivity is 1.36×10 14 Jones. Piezo-phototronic effect is induced by monocrystalline CsPbBr3 nanowires, a 11.3x modulation of Iph is achieved.. A new design of photodetector is illustrated for high performance, low energy consumption and multifunction integration.